Prevalence and intensity of Allocreadium isoporum (Digenea: Allocreadiidae) in three endemic species of cyprinids (Capoeta spp.) in Turkey, in relation to season, host size and sex - Aydogdu, Ali; PEREZ-PONCE DE LEON, Gerardo; EMRE, YILMAZ; EMRE, NESRİN; Yabaci, AYŞEGÜL; YABACI TAK, AYŞEGÜL (My University, 2018)
Three species of cyprinids, i.e., Capoeta antalyensis (n=112), C. caelestis (n=99) and C. angorae (n=178) were collected from the Anatolian Region of Turkey to carry out this investigation. A total of 389 specimens of Capoeta were examined for Allocreadium isoporum infections throughout the four different seasons of 2012. The prevalence and mean intensity of infection of A. isoporum was investigated in relation to the host species, the seasons across the year, host size, and sex. Two-hundred and twenty-two specimens of a trematode identified as A. isoporum were found in these fishes. One-hundred seventy-eight C. angorae were caught, and 70 A. isoporum were recorded in 8 of 178 fish examined, with prevalence and mean intensity of infection of 4.49% and 8.7% parasites per infected fish, respectively. In the 112 specimens of C. antalyensis, 73 individuals of A. isoporum were found, with a prevalence of 19.6% and a mean intensity of 3.3. As for the infection in C. caelestis, a total of 79 specimens of A. isoporum were found in 17 of the 99 fish examined, with prevalence and mean intensity of infection of 17.1% and 4.6%, respectively. Prevalence and mean intensity values in relation to host size and sex, as well as the seasonality of infections was analyzed and the results were compared with other studies. The trematode A. isoporum is reported for the first time parasitising three endemic species of Capoeta spp. in Turkey, adding to the knowledge of geographical distribution and host range of this trematode species.